Scientific Opinion on Flavouring Group Evaluation 71 Revision 1 (FGE.71Rev1): consideration of aliphatic, linear, α, β‐unsaturated alcohols, aldehydes, carboxylic acids, and related esters evaluated by JECFA (63rd and 69th meeting) structurally related to flavouring substances evaluated in FGE.05Rev3. (9th January 2020) - ,; Younes, Maged; Aquilina, Gabriele; Castle, Laurence; Engel, Karl‐Heinz; Fowler, Paul; Frutos Fernandez, Maria Jose; Fürst, Peter; Gundert‐Remy, Ursula; Gürtler, Rainer; Husøy, Trine; Moldeus, Peter; et al.
Abstract: The EFSA Panel on Food Additives and Flavourings was requested to evaluate 39 flavouring substances assigned to the Flavouring Group Evaluation 71 (FGE.71), using the Procedure in Commission Regulation (EC) No 1565/2000. Nine substances have already been considered in FGE.71 [FL‐no: 08.054, 08.073, 08.123, 09.037, 09.156, 09.157, 05.158, 09.235, 09.239]. The remaining 30 substances [FL‐no: 02.020, 02.050, 02.090, 02.112, 02.137, 02.156, 02.210, 05.037, 05.060, 05.070, 05.073, 05.076, 05.078, 05.102, 05.109, 05.150, 05.171, 05.179, 09.276, 09.277, 09.303, 09.385, 09.394, 09.395, 09.396, 09.397, 09.398, 09.399, 09.678 and 09.841] have been cleared with respect to genotoxicity in FGE.200Rev1 and they are considered in this revision. The substances were evaluated through a stepwise approach that integrates information on the structure–activity relationships, intake from current uses, toxicological threshold of concern (TTC), and available data on metabolism and toxicity. The Panel concluded that none of the 39 substances gives rise to safety concerns at their levels of dietary intake, estimated on the basis of the 'Maximised Survey‐derived Daily Intake' (MSDI) approach. Besides the safety assessment of the flavouring substances, the specifications for the materials of commerce have also been considered and found adequate, except for [FL‐no: 08.073 and 09.235]. For these two substances, data on the composition of the stereoisomeric mixture should be requested. Normal and maximum use levels should be provided for nine flavouring substances [FL‐no: 08.054, 08.073, 08.123, 09.037, 09.156, 09.157, 05.158, 09.235, 09.239]. For two flavouring substances [FL‐no: 02.020 and 05.076], the 'modified Theoretical Added Maximum Daily Intake' (mTAMDI) estimates are above the TTC for their structural class I. Therefore, additional information on uses and use levels should be provided for these eleven substances in order to finalise their evaluation.